Recent status and future prospects of emerging oxygen vacancy-/defect-rich electrode materials: from creation mechanisms to detection/quantification techniques, and their electrochemical performance for rechargeable batteries - Sandeep Kumar Sundriyal; Yogesh Sharma (JPhys Energy)
Over the last few years, keen interest has been taken in creating and tuning the concentration of oxygen vacancies in electrode materials to enhance their performance and to develop next-generation rechargeable batteries. Oxygen vacancies can be created in electrode materials by using various synthesis techniques. Furthermore, controlled generation of oxygen vacancies in electrode materials plays an essential role in enhancing their electrochemical properties. However, controlled creation of oxygen vacancies in electrode materials via facile techniques is still a challenge. Furthermore, the characterization techniques available to quantify the exact amount and type of oxygen vacancies present in the bulk as well as the surface of a material are not appropriate. Hence, in this review, we have comprehensively summarized the recent reports on oxygen vacancy-based electrode materials and their impact on the electrochemical performance of rechargeable batteries. Furthermore, the challenges and prospects of these oxygen vacancy-rich electrode materials are also discussed.